High-Energy-Density Hydrochar and Bio-Oil from Hydrothermal Processing of Spent Coffee Grounds—Experimental Investigation - Mariusz Wądrzyk; Jakub Katerla; Rafał Janus; Marek Lewandowski; Marek Plata; Łukasz Korzeniowski (Energies)
Spent coffee grounds (SCGs), a by-product of coffee brewing, have high application potential. However, their high moisture content complicates conventional conversion without energy-intensive drying. This study explores a new route to convert SCGs to high-carbon bioproducts, such as hydrochar and bio-oil, through hydrothermal processing. The effect of the processing variables, i.e., temperature, residence time, and the application of the binary solvent as a reaction medium, on the distribution of the resultant bioproducts was investigated. The quality of the fabricated bioproducts was analyzed by means of instrumental techniques such as EA, ATR-FTIR, GC-MS, and GC-TCD-FID. Two dominant fractions were liquid bio-oil and solid hydrochar. The highest char yield (39 wt.%) was observed under milder conditions (low T and short residence times), while more severe conditions led to an increase in bio-oil formation, which reached a maximum of 46 wt.%. The resulting bio-oils were of similar quality, presenting high carbon content (71–74 wt.%) and energetic values (approximately 35 MJ/kg). Also, hydrochars showed a noticeable energy densification compared to raw materials, where the C content and HHV reached up to 73.8 wt.% and 30 MJ/kg, respectively. The addition of co-solvent to water improves the bio-oil yield as a result of the enhanced stabilization of reactive intermediates.